Embodying Bodies in Bernardine Evaristo’s Girl, Woman, Other (2019) - Alice Laurentino (VIA PANORAMICA: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2024)
ABSTRACT: The 2019 novel Girl, Woman, Other by Bernardine Evaristo tackles concerns prevalent in contemporary society. Because the body is such an elemental factor in the novel, as it has become in different realms of life, the bodies of its twelve characters serve as a canvas through which various class, gender, ethnical, sexual, and religious paradigms are presented and questioned. This article intends to explore, through an intersectional lens, the experiences lived by some of these womxn which are reflected, conditioned and filtered through their bodies. It focuses on the role of the body as both a vessel for expression and/or oppression of identity, separately, having in mind that these womxn are (second-generation) immigrants of differing ages and socio-economic backgrounds.